Unexpected Trend Deviation in Isoelectronic Transition Metal Borides A3T5B2 (A = group 4, T = group 9): Ti3Co5B2‐ vs. Perovskite‐Type Studied by Experiments and DFT Calculations. Issue 21 (9th October 2017) - Shankhari, Pritam; Scheifers, Jan P.; Hermus, Martin; Yubuta, Kunio; Fokwa, Boniface P. T.
Abstract : We present the first bulk synthesis of Ti3 Co5 B2, which was realized by arc‐melting a Co‐rich elemental mixture. Our X‐ray diffraction studies revealed a Ti/Co mixed occupancy on one of two possible Ti sites suggesting a phase width with x = 0–0.52 in Ti3– x Co5+ x B2 . Moreover, we studied experimentally and theoretically the isoelectronic substitution of Ti and Co by their respective higher homologues (Zr/Rh and Hf/Ir). Surprisingly, Ti3 Co5 B2 ‐type phase was obtained only for the Hf/Ir combination (single crystal analysis of Hf3 Ir5 B2 ), whereas for Zr/Rh a perovskite‐like phase (ZrRh3 Bx ) was discovered instead. We found that small but crucial differences (atomic radius ratio and electronegativity difference) between elements of the same group in the periodic Table are responsible for the unexpected trend deviation. This finding is supported by DFT calculations of the free energy of formation. Abstract :